The Effect of IAA-Producing and Phosphate-Solubilizing Bacteria Isolated from Zea mays Rhizosfera on the Germination of Vigna sinensis L (Wulung Var.) - Sari, Neti Kumala; Zulkifli, Lalu; Rasmi, Dewa Ayu Citra; Sedijani, Prapti (Jurnal Biologi Tropis, 2025)
PGPR are beneficial bacteria that play a role in increasing plant growth and productivity through hormone synthesis and provision of dissolved nutrients that are readily absorbed by plant roots. This study aims to determine the effect of IAA-producing and phosphate-solubilizing bacteria from corn plants (Zea mays L.) on the germination of legume plants (Vigna sinensis L.) in vitro. Rhizosphere bacteria from corn plants were isolated from Tetebatu Village, Sikur District, East Lombok Regency. IAA production and phosphate solubilization tests were carried out qualitatively and quantitatively. Qualitative phosphate solubilization was carried out by measuring the clear zone formed on Pikovskaya solid media and quantitatively using a spectrophotometer method with a wavelength of 690 nm. The test of the effect of bacteria on the germination of Wulung variety long bean plants planted on modified Murphy media with parameters of plant height, root length, fresh weight and dry weight of plants for 5 days was then analyzed using One Way Anova. The results showed that 7 isolates were able to produce IAA and dissolve phosphate and 3 other isolates were only able to dissolve phosphate. The highest IAA production (29.17 ppm) was produced by isolate RJ5 on the 5th day of incubation. The highest phosphate solubilization (18.46 ppm) was produced by isolate RJ1 on the 8th day of incubation. The results of the analysis showed that the effect of IAA-producing bacteria and phosphate-solubilizing bacteria on the germination of long bean plants was significantly different for plant height parameters, but not significantly different for root length, fresh weight and dry weight of plants. It can be concluded that bacteria isolated from the rhizosphere of corn (Zea mays) with the codes RJI and RJ5 are able to increase plant growth so that they have the potential as biofertilizer candidates that can be developed in the future.